Aerodynamic design and aircraft family concept for an advanced technology regional aircraft (ATRA) - Prasetyo, Edi; Arora, Prithvi Raj; Mohammad Saleem (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/